Analyzing Geographical Events Map Reduce - Anitha, G; Jyothi, K; Susmitha Valli, G; Karthik, R; Padmaja, B (International Journal of Engineering and Technology, 2018)
The huge information gathers huge volume of information; it is extraordinary computational test for the huge Hadoop information to keep up and process this information and furthermore removes valuable data in a proficient way. Land occasions will occur far and wide as one of the primary worldwide risks expanding under worldwide environmental change lately. Which raise the significance of avalanche events, with the point of diminishing their results we are utilizing Guide Lesson for dissecting these occasions in various regions in like manner with period.Â Â